Implementation of Nanocarriers for Brain-Specific Drug Delivery System - Sharma, Aditya; Alam, Md. Aftab; Kaur, Awaneet (Current Nanomaterials, 2025)
There are several safeguards in place to protect the brain from injury because of its vulnerability. Two major barriers prevent harmful substances from entering the brain: the blood-brain barrier (BBB) and the blood-cerebrospinal fluid barrier (BCSFB). Although there has been some success in devising ways for transporting medicines to the brain, the great majority of the nanoparticles (NPs) used in these procedures are destroyed in the process. An awareness of the whole scope of the delivery process and the numerous obstacles it may offer is necessary for the sensible design of brain-targeted pharmaceutical delivery systems. The blood-brain barrier (BBB) is the best-known physiological barrier affecting both brain access and the efficacy of various pharmacological therapies. Accordingly, the development of a promising therapy for the treatment of brain disorders requires drug targeting of the brain, specifically damaged cells. Researchers are looking into nano-carrier systems, also called surface-modified target-specific novel carrier systems, to determine if they can be used to boost the effectiveness of brain drugs while minimizing their side effects. These strategies have the potential to bypass BBB function, leading to increased drug levels in the brain. Numerous physiological parameters, such as active efflux transport, the brain's protein corona, nanocarrier stability and toxicity, physicochemical features, patient-related factors, and others, determine whether or not a novel carrier system is functional.
Keywords: novel carrier system